Solid oxide fuel cell electrolyte film and preparation method thereof

By combining solid-liquid phase molding and vacuum sputtering deposition processes in the electrolyte film of solid oxide fuel cells, a transition layer, a self-healing layer, and a dense layer are prepared, solving the problem that electrolyte films are difficult to densify and apply over large areas at low temperatures in the prior art. This achieves the preparation of electrolyte films with low energy consumption, high uniformity, and durability.

CN121507023APending Publication Date: 2026-02-10NANOFILM VACUUM COATING SHANGHAI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411041930.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-07-31
Publication Date
2026-02-10

AI Technical Summary

Technical Problem

Existing technologies struggle to prepare dense and thin solid oxide fuel cell electrolyte films at low temperatures, and these films are prone to pore formation during high-temperature operation, making it difficult to achieve large-area uniform deposition and commercial applications.

Method used

A transition layer was prepared using a solid-liquid phase molding process, and a self-healing layer and a dense layer were formed by combining it with a room temperature vacuum sputtering coating process. By controlling the sputtering process parameters, a dense electrolyte film was obtained at low temperature, which reduced energy consumption and improved the film-substrate adhesion.

Benefits of technology

It enables the preparation of dense and thin electrolyte films at lower temperatures, suitable for large-area applications, reducing energy consumption costs, and improving the uniformity and durability of the film. It is applicable to a variety of substrate types.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121507023A_ABST
    Figure CN121507023A_ABST
Patent Text Reader

Abstract

The invention discloses a solid oxide fuel cell electrolyte thin film and a preparation method thereof, the electrolyte thin film sequentially comprising a transition layer, a self-repairing layer and a compact layer is formed on the surface of one side of a substrate, the transition layer is made into a film through a solid-liquid phase forming process, and first sintering is carried out to obtain the solid oxide fuel cell electrolyte thin film, the self-repairing layer and the compact layer are obtained through the vacuum sputtering coating process at the room temperature, and the compact and thin electrolyte film is obtained at the low preparation temperature, so that the energy consumption cost can be reduced, and commercialized application is facilitated. According to the preparation method, relatively good film-substrate binding force and film compactness can be realized, pores and cracks are not easy to generate under extreme conditions, and the prepared electrolyte film is relatively flat in surface and can realize relatively good interface contact.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of solid oxide fuel cell technology, and in particular to a solid oxide fuel cell electrolyte thin film and its preparation method. Background Technology

[0002] Solid oxide fuel cells (SOFCs) possess advantages such as high energy conversion efficiency, wide fuel adaptability, and low cost, making them widely applicable in large-scale stationary power generation, residential cogeneration systems, and portable power sources. The solid oxide electrolyte is a key component of SOFCs, typically requiring sufficient density, high ionic conductivity, low internal resistance, and strong binding. To achieve high ionic conductivity, SOFCs often operate at temperatures between 800 and 1000°C. However, such high temperatures accelerate material aging, shorten battery life, and also pose safety hazards. Therefore, fabricating thin-film electrolytes with thin film thickness, low internal resistance, and high density is one method to reduce the operating temperature of SOFCs.

[0003] Currently, commonly used electrolyte materials for SOFCs include YSZ, ScSZ, and GDC. Traditional solid-liquid phase molding electrolyte manufacturing processes, such as screen printing, spin coating, dip coating, inkjet printing, and casting, generally require thick electrolyte films with high internal resistance to ensure airtightness. These processes also necessitate high-temperature sintering at temperatures above 1300℃ to 1400℃, resulting in high energy consumption. Furthermore, the manufactured electrolytes are unsuitable for SOFC operation at lower operating temperatures, and the high-temperature sintering process causes varying degrees of deformation in the electrolyte film. Therefore, these methods have limitations in large-scale industrial applications.

[0004] In recent years, the application of physical deposition techniques such as sputtering, pulsed laser deposition, and atomic layer deposition (ALD) to fabricate thin-film SOFC electrolytes has attracted widespread attention from researchers. However, current research on physical deposition techniques for SOFC electrolytes requires surfaces with small pores and relatively flat surfaces to achieve good film-substrate adhesion and film density, thus limiting their application to small-area electrolyte preparation. When applied to large-area thin-film electrolyte preparation, problems such as difficulty in achieving uniform deposition and poor process reproducibility lead to a significant decline in electrolyte performance. Moreover, existing vacuum sputtering deposition techniques for electrolyte preparation often require deposition at approximately 700°C to improve film density, but high temperatures lead to energy consumption and equipment aging, resulting in high costs. Sometimes, sintering at temperatures above 1000°C is also necessary after deposition, consuming significant time and energy costs, which is detrimental to long-term commercial applications. Furthermore, electrolytes prepared using existing techniques are prone to developing porosity during high-temperature operation at relatively thin thicknesses, hindering practical commercial applications. Therefore, while reducing the electrolyte thickness and improving the binding force, it is still challenging to ensure its uniformity, airtightness, durability and electrochemical performance when it is prepared on a large area. Summary of the Invention

[0005] The purpose of this invention is to overcome the above-mentioned defects in the prior art and provide a solid oxide fuel cell electrolyte thin film and its preparation method.

[0006] To achieve the above objectives, the technical solution of the present invention is as follows:

[0007] The present invention provides a solid oxide fuel cell electrolyte film, wherein the electrolyte film is disposed on one side surface of a substrate and includes a transition layer, a self-healing layer and a dense layer disposed sequentially in a direction away from the substrate;

[0008] The transition layer is obtained by solid-liquid phase molding process and first sintering, and the self-healing layer and the dense layer are obtained by vacuum sputtering coating process at room temperature.

[0009] Furthermore, the transition layer is used to seal the pores present on the substrate surface, the self-healing layer is used to reduce the thermal mismatch stress caused by the mismatch of the material thermal expansion coefficients between the electrolyte film and the substrate, and to smooth the surface of the transition layer, and the dense layer is used to form a dense, pore-free surface of the electrolyte film to ensure airtightness.

[0010] Furthermore, the self-healing layer is formed by deposition of first coating particles and weakens the interatomic bonding force through a first vacuum sputtering coating process, providing mechanical compatibility for the electrolyte film, thereby reducing the thermal mismatch stress caused by the mismatch of the material thermal expansion coefficients between the electrolyte film and the substrate, and making the surface of the transition layer smooth through the filling effect of the first coating particles. The dense layer is formed by deposition of second coating particles and through a second vacuum sputtering coating process, making the particle size of the second coating particles smaller than that of the first coating particles, forming a dense crystal structure with tight arrangement and no pores on the surface of the self-healing layer, serving as the surface layer of the electrolyte film.

[0011] Furthermore, the electrolyte materials of the transition layer, the self-healing layer, and the dense layer may be the same or different; and / or, the transition layer includes one or more sub-transition layers, and the electrolyte materials of the multiple sub-transition layers may be the same or different; and / or, the self-healing layer includes one or more sub-self-healing layers, and the electrolyte materials of the multiple sub-self-healing layers may be the same or different; and / or, the dense layer includes one or more sub-dense layers, and the electrolyte materials of the multiple sub-dense layers may be the same or different.

[0012] Further, the electrolyte material of the transition layer, the self-healing layer, or the dense layer includes at least one of yttrium-doped zirconium oxide (YSZ), gadolinium-doped cerium oxide (GDC), yttrium-doped cerium oxide (YDC), and samarium-doped cerium oxide (SDC); and / or, the first sintering temperature is 700–1200°C; and / or, by making the sputtering power and process gas pressure of the first vacuum sputtering coating process greater than the sputtering power and process gas pressure of the second vacuum sputtering coating process, and during the... In the first vacuum sputtering coating process, an intermittent coating method is used to make the interatomic bonding force of the self-healing layer less than that of the dense layer, thereby obtaining a self-healing layer with weakened interatomic bonding force, and making the particle size of the second coating particles smaller than that of the first coating particles, and no annealing treatment is performed after completing the first vacuum sputtering coating process and the second vacuum sputtering coating process; and / or, the thickness of the transition layer is 5 to 30 μm, and the thickness of the self-healing layer and the dense layer is 30 nm to 1 μm.

[0013] Furthermore, the electrolyte film is also obtained by a second sintering after obtaining the dense layer, the temperature of which is 100-800°C.

[0014] The present invention also provides a method for preparing a solid oxide fuel cell electrolyte thin film, comprising:

[0015] Provide substrate;

[0016] An electrolyte film is formed on one side surface of the substrate, such that the electrolyte film includes a transition layer, a self-healing layer and a dense layer formed sequentially in a direction away from the substrate;

[0017] The transition layer is obtained by forming a film through a solid-liquid phase molding process and performing a first sintering process, and the self-healing layer and the dense layer are obtained by a vacuum sputtering coating process at room temperature.

[0018] Furthermore, the method for forming the transition layer specifically includes:

[0019] Electrolyte powder, binder and solvent are uniformly mixed as raw materials, and a thin film is prepared on the porous surface of the substrate by solid-liquid phase molding process. Then, the first sintering is carried out at 700 to 1200°C to obtain a transition layer with a thickness of 5 to 30 μm.

[0020] The method for forming the self-healing layer and the dense layer specifically includes:

[0021] A self-healing layer with a thickness of 30 nm to 1 μm is formed on the surface of the transition layer by a first vacuum sputtering deposition process; a dense layer with a thickness of 30 nm to 1 μm is formed on the surface of the self-healing layer by a second vacuum sputtering deposition process.

[0022] Specifically, by making the sputtering power and process gas pressure of the first vacuum sputtering coating process greater than those of the second vacuum sputtering coating process, and by using an intermittent coating method during the first vacuum sputtering coating process, the interatomic bonding force of the deposited self-healing layer is made less than that of the deposited dense layer, thereby obtaining a self-healing layer with weakened interatomic bonding force. Furthermore, the particle size of the second coating particles is made smaller than that of the first coating particles, so that the self-healing layer provides mechanical compatibility to the electrolyte film, reducing the thermal mismatch stress between the electrolyte film and the substrate caused by the mismatch in the coefficients of thermal expansion of the materials. The filling effect of the first coating particles also smooths the surface of the transition layer. By making the sputtering power and process gas pressure of the second vacuum sputtering coating process less than those of the first vacuum sputtering coating process, the deposition rate and particle size of the second coating particles are reduced, forming a dense, pore-free crystal structure on the surface of the self-healing layer as the surface layer of the electrolyte film.

[0023] In this process, no annealing treatment is performed after completing the first vacuum sputtering coating process and the second vacuum sputtering coating process.

[0024] Further, the solid-liquid phase molding process includes one or more combinations of casting, screen printing, spin coating, electrophoretic deposition, slurry 3D printing, dry molding, slip casting, centrifugal casting, sol-gel method, spraying, and spray pyrolysis; and / or, the electrolyte powder includes one of yttrium oxide-doped zirconium oxide, gadolinium oxide-doped cerium oxide, yttrium oxide-doped cerium oxide, and samarium oxide-doped cerium oxide; the binder includes one of ethyl cellulose, nitrocellulose, carboxymethyl cellulose, polyvinyl alcohol, and polyvinyl butyral; the solvent includes one of terpineol, 1,4-butyrolactone, glycerol, dibutyl phthalate, and tributyl citrate; and / or, the first sintering temperature is preferably 800–1100°C, more preferably 900–1100°C; and / or, the thickness of the transition layer is preferably 5–25 μm, more preferably 5–20 μm.

[0025] Furthermore, during the first vacuum sputtering coating process, the target sputtering power is 1–10 W / cm². 2 The preferred value is 2-8 W / cm. 2 Further preferred is 2-6 W / cm 2 The process gas pressure is 0.3–2 Pa, preferably 0.3–1.5 Pa, and more preferably 0.3–1 Pa; the flow rate of the working gas Ar during the process is 20–500 sccm, preferably 20–400 sccm, and more preferably 20–300 sccm; the flow rate of the working gas O2 during the process is below 300 sccm, preferably below 200 sccm, and more preferably below 100 sccm; the O2 / Ar mixing ratio is 1 / 300–1 / 1, preferably 1 / 200–1 / 3, and more preferably 1 / 100–1 / 4; the sputtering deposition rate is 20–300 nm / min, preferably 20–200 nm / min, and more preferably 20– 100 nm / min; target-substrate distance is 2–30 cm, preferably 3–25 cm, more preferably 4–20 cm; bias voltage is 0–-1200 V, preferably -20 V–-800 V, more preferably -50 V–-600 V; bias voltage duty cycle is 1–100%, preferably 5–80%, more preferably 10–60%; the coating process is intermittent, achieved by intermittently switching on and off the working gases O2 and Ar, and the ratio of process pause time to total process time is 1 / 50–1 / 3, preferably 1 / 40–1 / 3, more preferably 1 / 30–1 / 3; the thickness of the self-healing layer is preferably 100 nm–1 μm, more preferably 150 nm–900 nm;

[0026] During the second vacuum sputtering coating process, the target sputtering power is 0.01–3 W / cm². 2 Preferably, it is 0.05–2.5 W / cm².2 More preferably 0.1–2 W / cm 2 The process gas pressure is 0.05–1 Pa, preferably 0.05–0.8 Pa, and more preferably 0.05–0.5 Pa; the flow rate of the working gas Ar during the process is 20–500 sccm, preferably 20–400 sccm, and more preferably 20–300 sccm; the flow rate of the working gas O2 during the process is below 300 sccm, preferably below 200 sccm, and more preferably below 100 sccm; the O2 / Ar mixing ratio is 1 / 300–1 / 1, preferably 1 / 200–1 / 3, and more preferably 1 / 100–1 / 4; sputtering The coating rate is 0.5–50 nm / min, preferably 1–45 nm / min, and more preferably 5–30 nm / min; the target-substrate distance is 2–30 cm, preferably 3–25 cm, and more preferably 4–20 cm; the bias voltage is +200 V to -1200 V, preferably -20 V to -800 V, and more preferably -50 V to -600 V; the bias voltage duty cycle is 1–100%, preferably 5%–80%, and more preferably 10%–60%; the thickness of the dense layer is preferably 50 nm to 800 nm, and more preferably 100 nm to 600 nm.

[0027] The target material used in the first vacuum sputtering coating process or the second vacuum sputtering coating process includes one of the following: Y / Zr alloy, Gd / Ce alloy, Y / Ce alloy, Sm / Ce alloy, yttrium-doped zirconium oxide, gadolinium-doped cerium oxide, yttrium-doped cerium oxide, and samarium-doped cerium oxide.

[0028] The vacuum sputtering coating type includes one or more combinations of DC sputtering, radio frequency sputtering, DC reactive sputtering, radio frequency reactive sputtering, and DC pulse sputtering.

[0029] Furthermore, it also includes: after forming the dense layer, performing a second sintering on the obtained electrolyte film.

[0030] Furthermore, the second sintering temperature is 100–800°C, preferably 200–800°C, and even more preferably 300–700°C; the second sintering time is less than 10 hours, preferably less than 5 hours, and even more preferably less than 3 hours.

[0031] Furthermore, it also includes: performing ion cleaning on the substrate on which the transition layer is formed before performing the first vacuum sputtering coating process.

[0032] Furthermore, both the ion cleaning and the vacuum sputtering coating are performed at room temperature without heating.

[0033] As can be seen from the above technical solution, this invention forms an electrolyte film on one side surface of a substrate, comprising a transition layer, a self-healing layer, and a dense layer in sequence. The transition layer is formed using a solid-liquid phase molding process followed by a first sintering. The self-healing layer and the dense layer are obtained using a vacuum sputtering deposition process at room temperature. This achieves a dense and thin electrolyte film at a lower preparation temperature, thereby reducing energy consumption costs and facilitating commercial applications. Furthermore, by designing a combined electrolyte structure of the transition layer, self-healing layer, and dense layer, this invention is applicable to various types of substrate surfaces, achieving good film-substrate adhesion and film density. It is less prone to porosity and cracking under extreme conditions, and the resulting electrolyte film has a relatively smooth surface, enabling good interfacial contact. This invention has the following advantages:

[0034] (1) By combining traditional solid-liquid phase molding process with modern vacuum sputtering coating process, a dense and thin SOFC electrolyte film is obtained, thereby reducing internal resistance and increasing ionic conductivity to reduce the operating temperature of solid oxide fuel cells.

[0035] (2) With the thickness reduced, a dense SOFC electrolyte film without pores is obtained, which ensures airtightness and can effectively prevent the reaction gas from coming into direct contact.

[0036] (3) It can be used to prepare larger areas (e.g., 1-500 cm²). 2 The SOFC electrolyte film has good uniformity over a large area and excellent process reproducibility.

[0037] (4) The electrolyte thin film preparation process of the present invention is carried out at a relatively low temperature. The solid-liquid phase forming process adopts a lower sintering temperature (700-1200°C) than the conventional sintering temperature. The vacuum sputtering coating process uses room temperature film formation and does not require post-annealing after vacuum sputtering coating, thus obtaining a high-quality thin film, thereby reducing energy consumption costs and facilitating commercial application.

[0038] (5) The electrolyte film prepared by the present invention can achieve good film-substrate adhesion and film density on various types of substrate surfaces.

[0039] (6) The electrolyte film prepared by the present invention is not prone to pores and cracking after multiple high and low temperature cycles.

[0040] (7) The electrolyte film prepared by the method of the present invention has a small surface roughness and can achieve better upper interface contact. Attached Figure Description

[0041] Figure 1This is a schematic diagram of the structure of a solid oxide fuel cell electrolyte film according to a preferred embodiment of the present invention.

[0042] Figure 2 This is a schematic flowchart of a method for preparing a solid oxide fuel cell electrolyte thin film according to a preferred embodiment of the present invention.

[0043] Figure 3 This is a schematic diagram comparing the SEM test results of the YSZ transition layer and the electrolyte film surface prepared in Example 1 of the present invention.

[0044] Figure 4 This is a schematic diagram comparing the water contact angle test results of the YSZ transition layer and the electrolyte film surface prepared in Example 1 of the present invention.

[0045] Figure 5 This is a schematic diagram comparing the SEM test results of the YSZ transition layer and the electrolyte film surface prepared in Example 2 of the present invention. Detailed Implementation

[0046] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention. Unless otherwise defined, the technical or scientific terms used herein should have the ordinary meaning understood by those skilled in the art. The terms "comprising" and similar expressions used herein mean that the element or object preceding the word covers the element or object listed after the word and its equivalents, but does not exclude other elements or objects.

[0047] Traditional methods for preparing solid oxide fuel cell electrolyte films (SOFCs) using screen printing, spin coating, dip coating, and inkjet printing typically result in very thick films with high internal resistance to ensure airtightness. This makes them unsuitable for SOFC operation at lower temperatures and requires high-temperature sintering at 1300–1400°C, leading to high energy consumption. Furthermore, the films undergo varying degrees of deformation after high-temperature sintering, hindering commercialization. Existing vacuum sputtering coating techniques, while producing thinner films, are prone to porosity during high-temperature operation, limiting their commercial applicability. Moreover, current technologies struggle to achieve large-area coverage (e.g., 1–500 cm²). 2The uniform deposition of SOFC electrolyte films suffers from poor process reproducibility. Most existing vacuum sputtering deposition processes require increasing the deposition temperature (e.g., to 700℃) to improve film quality, but high temperatures lead to energy consumption and equipment aging, resulting in higher costs and hindering long-term commercial applications. Existing vacuum sputtering deposition processes require surfaces with small pores and relatively flat surfaces to achieve good film-substrate adhesion and film density, limiting their applicability to small areas and hindering large-scale production.

[0048] To address the aforementioned problems, this invention provides a solid oxide fuel cell electrolyte film and its preparation method. The method involves forming an electrolyte film on one side surface of a substrate, comprising a transition layer, a self-healing layer, and a dense layer sequentially. The transition layer is formed using a solid-liquid phase molding process followed by a first sintering. The self-healing layer and the dense layer are obtained through a vacuum sputtering deposition process at room temperature. This achieves a dense and thin electrolyte film at a relatively low preparation temperature. The electrolyte film prepared by this method is thin, suitable for complex substrate types, has a relatively low preparation temperature, requires no high-temperature post-treatment, and is less prone to cracking during high-temperature operation.

[0049] The specific embodiments of the present invention will be further described in detail below with reference to the accompanying drawings.

[0050] refer to Figure 1 The present invention provides a solid oxide fuel cell electrolyte film 2, wherein the electrolyte film 2 is disposed on the upper surface of a substrate 1 as shown in the figure. Furthermore, the electrolyte film 2 includes a transition layer 3, a self-healing layer 4, and a dense layer 5 sequentially disposed along a direction away from the upper surface of the substrate 1.

[0051] The transition layer 3 is obtained by solid-liquid phase molding and first sintering, while the self-healing layer 4 and the dense layer 5 are obtained by vacuum sputtering deposition at room temperature. The transition layer 3 is used to seal the pores on the surface of the substrate 1; the self-healing layer 4 is used to reduce the thermal mismatch stress between the electrolyte film 2 and the substrate 1 caused by the mismatch of the coefficients of thermal expansion of the materials, and to smooth the surface of the transition layer 3; the dense layer 5 is used to form a dense, pore-free surface of the electrolyte film 2 to ensure airtightness.

[0052] In some embodiments, substrate 1 includes a single-layer substrate or a multi-layer substrate. The single-layer substrate is a single-layer porous substrate composed of one of the following: porous metal oxides, ceramics, or doped ceramics. The multi-layer substrate is a multi-layer porous substrate composed of, in sequence, porous metals, alloys, metal oxides, ceramics, doped ceramics, catalysts, and mixtures thereof. The pore size of the upper surface of substrate 1 in contact with the electrolyte film 2 is generally required to be smaller than the maximum thickness of the electrolyte film 2 (e.g., 32 μm).

[0053] It should be noted that the present invention is applicable to different types of solid oxide fuel cells, such as electrolyte-supported SOFCs, anode-supported SOFCs, metal-supported SOFCs, cathode-supported SOFCs, ceramic support-supported SOFCs, etc. Depending on the form of battery support, the type and material of the substrate also vary, which affects the overall performance of the battery.

[0054] In some embodiments, the transition layer 3 is obtained by solid-liquid phase molding and first sintering, at a lower sintering temperature of 700–1200°C, which is lower than the conventional sintering temperature. The thickness of the transition layer 3 is 5–30 μm. The function of the transition layer 3 is to seal the pores of the substrate 1. However, since the prepared transition layer 3 is relatively thin and the above-mentioned low-temperature sintering is used, a small number of pores may still exist (Note: Electrolytes prepared by conventional solid-liquid phase molding processes need to be sintered at a temperature of 1300–1400°C to reduce porosity; the thickness of YSZ films prepared with electrolyte support is usually around 200 μm).

[0055] In some embodiments, the self-healing layer 4 is deposited on the upper surface of the transition layer 3 by first coating particles formed in the first vacuum sputtering coating process. The first vacuum sputtering coating process weakens the interatomic bonding force, making the self-healing layer 4 tough, so that the electrolyte film 2 as a whole is not easy to crack under high temperature and extreme environment. The self-healing layer 4 connects the transition layer 3 and the dense layer 5, providing mechanical compatibility for the entire electrolyte film 2, thereby reducing the thermal mismatch stress caused by the mismatch of the thermal expansion coefficients between the electrolyte film 2 and the substrate 1, making the entire electrolyte film 2 less prone to cracking under extreme conditions.

[0056] Furthermore, the self-healing layer 4 forms first coating particles with relatively large particle sizes. The filling effect of the first coating particles can block the pores that may exist on the surface of the transition layer 3 and act as a bridge. It can also help fill the gaps that may exist on the surface of the transition layer 3, thereby weakening the influence of morphology such as pores on the surface of the transition layer 3 and deformation caused after the first sintering. This makes the surface of the transition layer 3 smooth and results in a relatively smooth and dense self-healing layer 4.

[0057] In some embodiments, the dense layer 5 is formed by depositing relatively small and fine second coating particles formed in the second vacuum sputtering coating process. The second vacuum sputtering coating process makes the particle size of the second coating particles smaller than that of the first coating particles. The second coating particles form a dense crystal structure with tight arrangement and no pores on the surface of the self-healing layer 4. The formed dense layer 5 serves as the surface layer of the entire electrolyte film 2.

[0058] In some embodiments, the electrolyte materials of the transition layer 3, the self-healing layer 4, and the dense layer 5 may be the same or different.

[0059] In some embodiments, the transition layer 3 includes one or more sub-transition layers 3, and the electrolyte materials of the multiple sub-transition layers 3 may be the same or different.

[0060] In some embodiments, the self-healing layer 4 includes one or more sub-self-healing layers 4, and the electrolyte materials of the multiple sub-self-healing layers 4 may be the same or different.

[0061] In some embodiments, the dense layer 5 includes one or more sub-dense layers 5, and the electrolyte materials of the multiple sub-dense layers 5 may be the same or different.

[0062] In some embodiments, the electrolyte material of the electrolyte film 2 includes at least one selected from yttrium-doped zirconium oxide (YSZ), gadolinium-doped cerium oxide (GDC), yttrium-doped cerium oxide (YDC), and samarium-doped cerium oxide (SDC). Preferably, the electrolyte material of the electrolyte film 2 includes at least one selected from YSZ and GDC.

[0063] In some embodiments, the electrolyte material of the transition layer 3 includes at least one of YSZ, GDC, YDC, and SDC. Preferably, the electrolyte material of the transition layer 3 includes at least one of YSZ and GDC.

[0064] In some embodiments, the electrolyte material of the self-healing layer 4 includes at least one of YSZ, GDC, YDC, and SDC. Preferably, the electrolyte material of the self-healing layer 4 includes at least one of YSZ and GDC.

[0065] In some embodiments, the electrolyte material of the dense layer 5 includes at least one of YSZ, GDC, YDC, and SDC. Preferably, the electrolyte material of the dense layer 5 includes at least one of YSZ and GDC.

[0066] In some embodiments, by making the sputtering power and process gas pressure of the first vacuum sputtering coating process greater than the sputtering power and process gas pressure of the second vacuum sputtering coating process, and by using an intermittent coating method during the first vacuum sputtering coating process, the interatomic bonding force of the self-healing layer 4 is made less than the interatomic bonding force of the dense layer 5, thereby obtaining a self-healing layer 4 with weakened interatomic bonding force, and making the particle size of the second coating particles smaller than the particle size of the first coating particles.

[0067] In some embodiments, the thickness of the self-healing layer 4 and the dense layer 5 is 30 nm to 1 μm.

[0068] In some embodiments, no annealing treatment is performed after completing the first vacuum sputtering coating process and the second vacuum sputtering coating process. That is, no annealing treatment is performed after completing the first vacuum sputtering coating process and forming the self-healing layer 4. Similarly, no annealing treatment is performed after completing the second vacuum sputtering coating process and forming the dense layer 5. In other words, the electrolyte thin film 2 of the present invention not only has a relatively low preparation temperature, but also does not require high-temperature post-treatment.

[0069] In some embodiments, after obtaining the dense layer 5, the electrolyte film 2 is further obtained by a second sintering at a low temperature. The second sintering temperature is 100–800°C, and the second sintering time is less than 10 hours. By performing overall low-temperature sintering of the electrolyte film 2 after obtaining the dense layer 5, the bonding between the transition layer 3, the self-healing layer 4, and the dense layer 5 can be promoted, and film stress can be reduced, resulting in a higher quality electrolyte film 2.

[0070] The following detailed description, in conjunction with specific embodiments and accompanying drawings, provides a further detailed explanation of a method for preparing a solid oxide fuel cell electrolyte film 2 according to the present invention.

[0071] A method for preparing a solid oxide fuel cell electrolyte film 2 according to the present invention includes:

[0072] Substrate 1 is provided;

[0073] An electrolyte film 2 is formed on one side surface of the substrate 1, such that the electrolyte film 2 includes a transition layer 3, a self-healing layer 4 and a dense layer 5 formed sequentially in a direction away from the substrate 1.

[0074] In this process, a transition layer 3 is obtained by forming a film through a solid-liquid phase molding process and performing a first sintering. A self-healing layer 4 and a dense layer 5 are obtained by a vacuum sputtering coating process at room temperature.

[0075] refer to Figure 2 In some embodiments, the method for preparing a solid oxide fuel cell electrolyte film 2 according to the present invention can be used to prepare, for example... Figure 1 The solid oxide fuel cell electrolyte film 2 of the present invention is shown, and includes the following steps:

[0076] Step S1: Form a transition layer 3 on the surface of substrate 1.

[0077] Electrolyte powder, binder, and solvent are uniformly mixed and a thin film is prepared on the porous surface of substrate 1 using a solid-liquid phase molding process. Then, sintering is performed at a lower sintering temperature than conventional sintering (first sintering) to obtain a thin transition layer 3, such as... Figure 1 As shown.

[0078] The transition layer 3 is used to seal the pores on the surface of the substrate 1. Because the transition layer 3 is relatively thin and the aforementioned low-temperature sintering is used, a small number of pores may still exist. Electrolytes prepared using traditional solid-liquid phase molding processes require sintering at 1300–1400°C to reduce porosity; and YSZ films prepared with electrolyte support are typically about 200 μm thick.

[0079] In some embodiments, the substrate 1 includes, but is not limited to, a single-layer or multi-layer porous substrate 1 made of a porous metal, alloy, metal oxide, ceramic, doped ceramic, catalyst, or mixture thereof. The pore size of the upper surface of the substrate 1 in contact with the electrolyte film 2 is generally required to be less than the maximum thickness of the electrolyte film 2 (e.g., 32 μm).

[0080] In some embodiments, the solid-liquid phase molding process includes one or more combinations of casting, screen printing, spin coating, electrophoretic deposition, slurry 3D printing, dry molding, slip casting, centrifugal casting, sol-gel method, spraying, and spray pyrolysis. Preferably, the solid-liquid phase molding process includes casting, screen printing, and spin coating methods.

[0081] In some embodiments, the electrolyte powder raw material includes one of yttrium-doped zirconium oxide (YSZ), gadolinium-doped cerium oxide (GDC), yttrium-doped cerium oxide (YDC), samarium-doped cerium oxide (SDC), etc.

[0082] The binder includes one of the following: ethyl cellulose, nitrocellulose, carboxymethyl cellulose, polyvinyl alcohol, polyvinyl butyral, etc.

[0083] Solvents include one of the following: terpineol, 1,4-butyrolactone, glycerol, dibutyl phthalate, tributyl citrate, etc.

[0084] In some embodiments, the first sintering temperature is 700–1200°C. Preferably, the first sintering temperature is 800–1100°C. More preferably, the first sintering temperature is 900–1100°C.

[0085] In some embodiments, the thickness of the transition layer 3 is 5–30 μm. Preferably, the thickness of the transition layer 3 is 5–25 μm. More preferably, the thickness of the transition layer 3 is 5–20 μm.

[0086] Step S2: Form a self-healing layer 4 on the surface of the transition layer 3.

[0087] At room temperature, using electrolyte raw materials as the target material, a self-healing layer 4, which is thinner than the transition layer 3, is formed on the surface of the transition layer 3 by the deposition of first coating particles through a first vacuum sputtering coating process.

[0088] In some embodiments, the electrolyte raw material target used in the first vacuum sputtering coating process includes, but is not limited to, one of Y / Zr alloy, Gd / Ce alloy, Y / Ce alloy, Sm / Ce alloy, yttrium-doped zirconium oxide (YSZ), gadolinium-doped cerium oxide (GDC), yttrium-doped cerium oxide (YDC), and samarium-doped cerium oxide (SDC). Preferably, the electrolyte raw material target used in the first vacuum sputtering coating process includes one of Y / Zr alloy, Gd / Ce alloy, YSZ, and GDC.

[0089] In some embodiments, the first vacuum sputtering coating type includes one or more combinations of DC sputtering, radio frequency sputtering, DC reactive sputtering, radio frequency reactive sputtering, and DC pulse sputtering.

[0090] In some embodiments, at room temperature, the substrate 1 coated with the transition layer 3 is first subjected to ion cleaning, and then a first vacuum sputtering deposition process is used, in which an electrolyte raw material is used as the target material to deposit a self-healing layer 4 on the surface of the transition layer 3.

[0091] Both ion cleaning and the first vacuum sputtering coating were performed at room temperature without heating.

[0092] After obtaining the self-healing layer 4 through the first vacuum sputtering coating process, no annealing treatment is performed.

[0093] The self-healing layer 4 is a film layer mainly composed of large and medium-sized coated particles deposited by the deposition of first coated particles. During the sputtering process, by controlling the sputtering process, the interatomic bonding is weakened, resulting in a tough self-healing layer 4 that is not prone to cracking under high temperature and extreme environments. The self-healing layer 4 connects the transition layer 3 and the dense layer 5. This self-healing layer 4 provides mechanical compatibility for the entire electrolyte film structure, reduces the thermal mismatch stress caused by the mismatch in the coefficients of thermal expansion between the electrolyte and the substrate 1, and makes the entire electrolyte film 2 less prone to cracking under extreme conditions. Among them, the large coated particles in the self-healing layer 4 act as pore plugs and bridges, while the medium-sized coated particles help fill gaps, thereby weakening the influence of morphology such as porosity on the surface of the transition layer 3 and deformation after sintering, resulting in a relatively smooth and dense surface of the self-healing layer 4. Therefore, it can be used to prepare larger areas (e.g., 1-500 cm²). 2 The SOFC electrolyte membrane 2 has good uniformity over a large area and excellent process reproducibility.

[0094] In some embodiments, the relevant process parameters for performing the first vacuum sputtering coating process include:

[0095] The sputtering power of the target material is relatively high, ranging from 1 to 10 W / cm. 2 The preferred value is 2-8 W / cm. 2Further preferred is 2-6 W / cm 2 .

[0096] During the process, the process gas pressure is relatively high, ranging from 0.3 to 2 Pa, preferably from 0.3 to 1.5 Pa, and more preferably from 0.3 to 1 Pa; the flow rate of the process gas Ar is 20 to 500 sccm, preferably from 20 to 400 sccm, and more preferably from 20 to 300 sccm; the flow rate of the process gas O2 is below 300 sccm, preferably below 200 sccm, and more preferably below 100 sccm; the O2 / Ar mixing ratio is 1 / 300 to 1 / 1, preferably from 1 / 200 to 1 / 3, and more preferably from 1 / 100 to 1 / 4; and the sputtering deposition rate is relatively fast, ranging from 20 to 300 nm / min, preferably from 20 to 200 nm / min, and more preferably from 20 to 100 nm / min.

[0097] The target-substrate distance is 2–30 cm, preferably 3–25 cm, and more preferably 4–20 cm.

[0098] The bias voltage is 0 to -1200V, preferably -20V to -800V, and more preferably -50V to -600V; the bias voltage duty cycle is 1 to 100%, preferably 5 to 80%, and more preferably 10 to 60%.

[0099] The above-mentioned coating process is an intermittent coating process, which is achieved by intermittently switching on and off the working gas. O2 and Ar can be mixed in a mixing tank and then intermittently introduced into the sputtering chamber. The ratio of the process pause time to the total process time is 1 / 50 to 1 / 3, preferably 1 / 40 to 1 / 3, and more preferably 1 / 30 to 1 / 3.

[0100] The obtained self-healing layer 4 is as follows Figure 1 As shown. The thickness of the self-healing layer 4 is 30 nm to 1 μm, preferably 100 nm to 1 μm, and more preferably 150 nm to 900 nm.

[0101] Step S3: A dense layer 5 is formed on the surface of the self-healing layer 4 to form an electrolyte film 2.

[0102] At room temperature, using electrolyte raw materials as the target material, a dense layer 5, which is thinner than the transition layer 3, is formed on the surface of the self-healing layer 4 by the deposition of second coating particles.

[0103] In some embodiments, the electrolyte raw material target used in the second vacuum sputtering coating process includes, but is not limited to, one of Y / Zr alloy, Gd / Ce alloy, Y / Ce alloy, Sm / Ce alloy, yttrium-doped zirconium oxide (YSZ), gadolinium-doped cerium oxide (GDC), yttrium-doped cerium oxide (YDC), and samarium-doped cerium oxide (SDC). Preferably, the electrolyte raw material target used in the second vacuum sputtering coating process includes one of Y / Zr alloy, Gd / Ce alloy, YSZ, and GDC.

[0104] In some embodiments, the second vacuum sputtering coating type includes one or more combinations of DC sputtering, radio frequency sputtering, DC reactive sputtering, radio frequency reactive sputtering, and DC pulse sputtering.

[0105] The second vacuum sputtering deposition is performed at room temperature without heating. After obtaining the dense layer 5 through the second vacuum sputtering deposition process, no annealing treatment is performed.

[0106] The dense layer 5 is a film composed of fine second-coated particles. The dense layer 5 is generated by sputtering and deposited on the self-healing layer 4 at a slightly lower deposition rate to form a dense crystalline structure with tightly packed particles and no pinholes.

[0107] In some embodiments, the relevant process parameters for performing the second vacuum sputtering coating process include:

[0108] The sputtering power of the target is relatively low, ranging from 0.01 to 3 W / cm². 2 Preferably, it is 0.05–2.5 W / cm². 2 More preferably 0.1–2 W / cm 2 .

[0109] During the process, the process gas pressure is relatively low, ranging from 0.05 to 1 Pa, preferably from 0.05 to 0.8 Pa, and more preferably from 0.05 to 0.5 Pa; the flow rate of the working gas Ar is 20 to 500 sccm, preferably from 20 to 400 sccm, and more preferably from 20 to 300 sccm; the flow rate of the working gas O2 is below 300 sccm, preferably below 200 sccm, and more preferably below 100 sccm; the O2 / Ar mixing ratio is 1 / 300 to 1 / 1, preferably from 1 / 200 to 1 / 3, and more preferably from 1 / 100 to 1 / 4; the sputtering deposition rate is relatively slow, ranging from 0.5 to 50 nm / min, preferably from 1 to 45 nm / min, and more preferably from 5 to 30 nm / min.

[0110] The target-substrate distance is 2–30 cm, preferably 3–25 cm, and more preferably 4–20 cm; the bias voltage is +200 V to -1200 V, preferably -20 V to -800 V, and more preferably -50 V to -600 V; the bias voltage duty cycle is 1–100%, preferably 5% to 80%, and more preferably 10% to 60%.

[0111] The obtained dense layer 5 is as follows Figure 1 As shown. The thickness of the dense layer 5 is 30 nm to 1 μm, preferably 50 nm to 800 nm, and more preferably 100 nm to 600 nm.

[0112] Both the self-healing layer 4 and the dense layer 5 are prepared using electrolyte raw materials as targets and by vacuum sputtering deposition. The main difference lies in the different preparation processes.

[0113] Specifically, by using a higher sputtering power and process gas pressure in the first vacuum sputtering deposition process than in the second vacuum sputtering deposition process, and by employing an intermittent deposition method in the first vacuum sputtering deposition process, the interatomic bonding force of the deposited self-healing layer 4 is reduced compared to that of the deposited dense layer 5. This results in a self-healing layer 4 with weakened interatomic bonding force. Furthermore, the particle size of the second deposition particles is smaller than that of the first deposition particles. This provides mechanical compatibility for the electrolyte film 2 through the self-healing layer 4, reducing the thermal mismatch stress between the electrolyte film 2 and the substrate 1 caused by the mismatch in their coefficients of thermal expansion. The filling effect of the first deposition particles also smooths the surface of the transition layer 3. By using a lower sputtering power and process gas pressure in the second vacuum sputtering deposition process than in the first, the deposition rate and particle size of the second deposition particles are reduced, forming a dense, pore-free crystalline structure on the surface of the self-healing layer 4, which serves as the surface layer of the electrolyte film 2. Therefore, by reducing the thickness, a dense, non-porous SOFC electrolyte film 2 is obtained, ensuring airtightness and effectively preventing direct contact between reactant gases. Furthermore, the electrolyte film 2 prepared by the method of this invention has low surface roughness, enabling better upper interface contact.

[0114] It should be noted that the sputtering power used to prepare the self-healing layer 4 is higher than that used to prepare the dense layer 5. This is based on the principle that a higher sputtering power results in a larger target sputtering volume, more large sputtered particles, and a faster film deposition rate. This makes it more difficult for the first coating particles to migrate and diffuse on the substrate (transition layer 3) surface, easily forming layered or island-like clusters with weaker interatomic bonds, but still achieving the functions of plugging pores, bridging, and filling gaps. Conversely, the lower sputtering power and smaller target sputtering volume used to prepare the dense layer 5 make it easier to form finer second coating particles, thus making the film of the dense layer 5 even denser.

[0115] Furthermore, the sputtering pressure during the preparation of the self-healing layer 4 is higher than that during the preparation of the dense layer 5. The gas pressure is mainly determined by the base vacuum and the working gas flow rate during the coating process. During the preparation of the self-healing layer 4, the working gas is introduced intermittently, thus achieving intermittent coating. The resulting self-healing layer 4 has weak atomic bonding, connecting the transition layer 3 and the dense layer 5, and providing mechanical compatibility for the entire electrolyte film 2 structure. In the preparation of the dense layer 5, the high vacuum and low working gas volume increase the free path of gas molecules, making it less prone to forming island clusters and more likely to form a uniform and dense film.

[0116] Furthermore, the sputtering deposition rate for preparing the self-healing layer 4 is higher than that for preparing the dense layer 5. To mitigate the influence of surface porosity in the transition layer 3 and obtain a film with weak atomic bonding, a faster deposition rate is required for preparing the self-healing layer 4. However, for preparing the dense layer 5, a flat, uniform, and dense plane is needed to facilitate subsequent battery processing. Therefore, fine second-layer deposition particles are required to allow sufficient time for migration and diffusion after deposition, necessitating a lower deposition rate for preparing the dense layer 5.

[0117] This invention provides a low-temperature preparation method for a self-healing large-area solid oxide fuel cell electrolyte film 2. In order to reduce the preparation temperature and the overall electrolyte film thickness, this invention combines the traditional solid-liquid phase forming process with the vacuum sputtering coating process, thereby obtaining a denser electrolyte with a thinner film at a lower preparation temperature, thus reducing energy consumption costs and facilitating commercial applications.

[0118] This invention also utilizes a combined electrolyte structure consisting of a self-healing layer 4, a transition layer 3, and a dense layer 5. This design makes the preparation process applicable to various types of substrate surfaces, achieving good film-substrate adhesion and film density. Even under extreme conditions (e.g., after multiple high and low temperature cycles), it is not prone to porosity or cracking. Furthermore, the resulting electrolyte film 2 has a relatively smooth surface, enabling good interfacial contact.

[0119] In some embodiments, step S4 is further included: after forming the dense layer 5, the obtained electrolyte film 2 is subjected to a second sintering.

[0120] After the transition layer 3, self-healing layer 4, and dense layer 5 are prepared, the electrolyte film 2 is subjected to a second sintering at a low temperature to promote the bonding between the film layers, reduce the film layer stress, and thus obtain a higher quality electrolyte film 2.

[0121] In some embodiments, the temperature of the second sintering is 100–800°C, preferably 200–800°C, and more preferably 300–700°C.

[0122] In some embodiments, the second sintering time is 10 hours or less, preferably 5 hours or less, and more preferably 3 hours or less.

[0123] Example 1

[0124] (1) Preparation of AAO / NiO-YSZ porous substrate 1: Prepare a porous alumina substrate with a size of 20cm×20cm. After cleaning and drying, NiO-YSZ anode material is deposited on the porous alumina substrate by reactive co-sputtering of Ni and Y-Zr alloy target to obtain porous substrate 1.

[0125] (2) Preparation of YSZ transition layer 3: The ball-milled YSZ powder and terpineol ethyl cellulose binder were mixed in a 7:3 ratio and stirred until homogeneous to obtain a YSZ slurry. The YSZ slurry was uniformly coated onto the AAO / NiO-YSZ porous substrate 1 using screen printing. Subsequently, the YSZ transition layer 3 was sintered at 1100℃ for 3 hours, resulting in a YSZ transition layer 3 with a thickness of 10 μm. Its surface SEM test results are as follows: Figure 3 As shown in (a), the water contact angle CA is 44.442, as... Figure 4 As shown in (a), it can be seen that the electrolyte membrane with only the transition layer 3 still has pores and is relatively hydrophilic.

[0126] (3) Preparation of YSZ self-healing layer 4: Under room temperature conditions, the substrate 1 with deposited YSZ transition layer 3 was first ion-cleaned, and then radio frequency magnetron sputtering was performed using "8mol% Y2O3-92mol% ZrO2" as a mixed target material, with a sputtering power of 5W / cm. 2 The working gas pressure was 0.5 Pa, the Ar flow rate was 200 sccm, the O2 flow rate was 30 sccm, the coating rate was 30 nm / min, the target-substrate distance was 8 cm, the bias voltage was -500 V, the duty cycle was 40%, and the coating process was intermittent, with the process running for 5 min and then pausing for 1 min, alternating between the two. The resulting self-healing layer 4 had a thickness of 600 nm.

[0127] (4) Preparation of YSZ dense layer 5: Using "8mol% Y2O3-92mol% ZrO2" as the target material, radio frequency magnetron sputtering was performed at room temperature with a sputtering power of 1W / cm. 2 The working gas pressure was 0.2 Pa, the Ar flow rate was 50 sccm, the coating rate was 15 nm / min, the target-substrate distance was 8 cm, the bias voltage was -500 V, the duty cycle was 30%, and the thickness of the resulting dense layer 5 was 300 nm.

[0128] No further post-processing is required to obtain a smooth and dense YSZ electrolyte film 2, the structure of which can be referenced. Figure 1 The surface SEM test results are as follows: Figure 3 As shown in b, the water contact angle CA is 97.37. Figure 4 As shown in b, the obtained electrolyte film 2 is dense, non-porous, and relatively hydrophobic. The prepared YSZ electrolyte film 2 showed no cracking after being treated at 650℃ for 100 hours.

[0129] Example 2

[0130] (1) Preparation of NiO-YSZ porous substrate 1: NiO-YSZ porous support substrate 1 with a size of 20cm×20cm was prepared by tape casting.

[0131] (2) Preparation of YSZ transition layer 3: The ball-milled YSZ and terpineol carboxymethyl cellulose binder were mixed in a 6:4 ratio and stirred until homogeneous to obtain a YSZ slurry. The YSZ slurry was uniformly coated onto the NiO-YSZ porous substrate 1 using a spraying method, followed by low-temperature sintering at 900℃ for 2 hours. The resulting YSZ transition layer 3 had a thickness of 15 μm. Its SEM test results are as follows: Figure 5 As shown in a.

[0132] (3) Preparation of YSZ self-healing layer 4: Under room temperature conditions, the substrate 1 with deposited YSZ transition layer 3 was first ion-cleaned, and then radio frequency magnetron sputtering was performed using "8mol% Y2O3-92mol% ZrO2" as the target material, with a sputtering power of 3W / cm. 2 The working gas pressure was 0.6 Pa, the Ar flow rate was 200 sccm, the O2 flow rate was 50 sccm, the coating rate was 40 nm / min, the target-substrate distance was 8 cm, the bias voltage was -500 V, the duty cycle was 40%, and the coating process was intermittent, with the process running for 5 min, paused for 30 s, and repeated alternately. The resulting self-healing layer 4 had a thickness of 800 nm.

[0133] (4) Preparation of YSZ dense layer 5: Using "8mol% Y2O3-92mol% ZrO2" as the target material, radio frequency magnetron sputtering was performed at room temperature, with an electrolyte film sputtering power of 0.5W / cm. 2 The working gas pressure was 0.1 Pa, the Ar flow rate was 100 sccm, the O2 flow rate was 25 sccm, the coating rate was 20 nm / min, the target-substrate distance was 8 cm, the bias voltage was -500 V, the duty cycle was 30%, and the thickness of the resulting dense layer 5 was 400 nm.

[0134] (5) Perform low-temperature sintering at 500℃ for 1 hour to obtain a uniform and dense YSZ electrolyte film 2, the structure of which can be referenced. Figure 1 Its SEM test results are as follows Figure 5As shown in b. The prepared YSZ electrolyte film 2 was subjected to high-temperature treatment at 650℃ for 100h, and no cracking was observed.

[0135] In summary, this invention forms an electrolyte film 2 on one side surface of a substrate 1, comprising a transition layer 3, a self-healing layer 4, and a dense layer 5 sequentially. The transition layer 3 is formed using a solid-liquid phase molding process followed by a first sintering. The self-healing layer 4 and the dense layer 5 are obtained using a vacuum sputtering deposition process at room temperature. This achieves a dense and thin electrolyte film 2 at a lower preparation temperature, thereby reducing energy consumption costs and facilitating commercial applications. Furthermore, the combined electrolyte structure of the transition layer 3, self-healing layer 4, and dense layer 5 is applicable to various types of substrate surfaces, achieving good film-substrate adhesion and film density. It is less prone to porosity and cracking under extreme conditions, and the resulting electrolyte film 2 has a relatively smooth surface, enabling good interfacial contact. Applying the SOFC electrolyte film 2 of this invention can reduce internal resistance and increase ionic conductivity, thereby lowering the operating temperature of the SOFC.

[0136] While embodiments of the present invention have been described in detail above, it will be apparent to those skilled in the art that various modifications and variations can be made to these embodiments. However, it should be understood that such modifications and variations fall within the scope and spirit of the invention as set forth in the claims. Furthermore, the invention described herein may have other embodiments and can be implemented or carried out in various ways.

Claims

1. A solid oxide fuel cell electrolyte membrane, characterized in that, The electrolyte film is disposed on one side surface of the substrate and includes a transition layer, a self-healing layer and a dense layer arranged sequentially in a direction away from the substrate; The transition layer is obtained by solid-liquid phase molding process and first sintering, and the self-healing layer and the dense layer are obtained by vacuum sputtering coating process at room temperature.

2. The solid oxide fuel cell electrolyte membrane according to claim 1, characterized in that, The transition layer is used to seal the pores present on the substrate surface. The self-healing layer is used to reduce the thermal mismatch stress caused by the mismatch of the material thermal expansion coefficients between the electrolyte film and the substrate, and to smooth the surface of the transition layer. The dense layer is used to form a dense, pore-free surface of the electrolyte film to ensure airtightness.

3. The solid oxide fuel cell electrolyte membrane according to claim 2, characterized in that, The self-healing layer is formed by deposition of first coating particles and weakens the interatomic bonding force through a first vacuum sputtering coating process, providing mechanical compatibility for the electrolyte film, thereby reducing the thermal mismatch stress caused by the mismatch of the material thermal expansion coefficients between the electrolyte film and the substrate, and making the surface of the transition layer smooth through the filling effect of the first coating particles. The dense layer is formed by deposition of second coating particles and through a second vacuum sputtering coating process, making the particle size of the second coating particles smaller than that of the first coating particles, forming a dense crystal structure with tight arrangement and no pores on the surface of the self-healing layer, which serves as the surface layer of the electrolyte film.

4. The solid oxide fuel cell electrolyte membrane according to claim 3, characterized in that, The electrolyte materials of the transition layer, the self-healing layer, and the dense layer may be the same or different; and / or, the transition layer includes one or more sub-transition layers, and the electrolyte materials of the multiple sub-transition layers may be the same or different; and / or, the self-healing layer includes one or more sub-self-healing layers, and the electrolyte materials of the multiple sub-self-healing layers may be the same or different; and / or, the dense layer includes one or more sub-dense layers, and the electrolyte materials of the multiple sub-dense layers may be the same or different.

5. The solid oxide fuel cell electrolyte membrane according to claim 3, characterized in that, The electrolyte material of the transition layer, the self-healing layer, or the dense layer includes at least one of yttrium-doped zirconium oxide, gadolinium-doped cerium oxide, yttrium-doped cerium oxide, and samarium-doped cerium oxide; and / or, the first sintering temperature is 700–1200°C; and / or, by making the sputtering power and process gas pressure of the first vacuum sputtering coating process greater than the sputtering power and process gas pressure of the second vacuum sputtering coating process, and by using an intermittent coating method during the first vacuum sputtering coating process, the interatomic bonding force of the self-healing layer is less than that of the dense layer, thereby obtaining a self-healing layer with weakened interatomic bonding force, and making the particle size of the second coating particles smaller than that of the first coating particles, and by not performing annealing treatment after completing the first and second vacuum sputtering coating processes; and / or, the thickness of the transition layer is 5–30 μm, and the thickness of the self-healing layer and the dense layer is 30 nm–1 μm.

6. The solid oxide fuel cell electrolyte membrane according to claim 1, characterized in that, The electrolyte film is also obtained by a second sintering process after obtaining the dense layer, wherein the temperature of the second sintering is 100–800°C.

7. A method for preparing a solid oxide fuel cell electrolyte thin film, characterized in that, include: Provide substrate; An electrolyte film is formed on one side surface of the substrate, such that the electrolyte film includes a transition layer, a self-healing layer and a dense layer formed sequentially in a direction away from the substrate; The transition layer is obtained by forming a film through a solid-liquid phase molding process and performing a first sintering process, and the self-healing layer and the dense layer are obtained by a vacuum sputtering coating process at room temperature.

8. The method for preparing a solid oxide fuel cell electrolyte thin film according to claim 7, characterized in that, The method for forming the transition layer specifically includes: Electrolyte powder, binder and solvent are uniformly mixed as raw materials, and a thin film is prepared on the porous surface of the substrate by solid-liquid phase molding process. Then, the first sintering is carried out at 700 to 1200°C to obtain a transition layer with a thickness of 5 to 30 μm. The method for forming the self-healing layer and the dense layer specifically includes: A self-healing layer with a thickness of 30 nm to 1 μm is formed on the surface of the transition layer by a first vacuum sputtering deposition process; a dense layer with a thickness of 30 nm to 1 μm is formed on the surface of the self-healing layer by a second vacuum sputtering deposition process. Specifically, by making the sputtering power and process gas pressure of the first vacuum sputtering coating process greater than those of the second vacuum sputtering coating process, and by using an intermittent coating method during the first vacuum sputtering coating process, the interatomic bonding force of the deposited self-healing layer is made less than that of the deposited dense layer, thereby obtaining a self-healing layer with weakened interatomic bonding force. Furthermore, the particle size of the second coating particles is made smaller than that of the first coating particles, so that the self-healing layer provides mechanical compatibility to the electrolyte film, reducing the thermal mismatch stress between the electrolyte film and the substrate caused by the mismatch in the coefficients of thermal expansion of the materials. The filling effect of the first coating particles also smooths the surface of the transition layer. By making the sputtering power and process gas pressure of the second vacuum sputtering coating process less than those of the first vacuum sputtering coating process, the deposition rate and particle size of the second coating particles are reduced, forming a dense, pore-free crystal structure on the surface of the self-healing layer as the surface layer of the electrolyte film. In this process, no annealing treatment is performed after completing the first vacuum sputtering coating process and the second vacuum sputtering coating process.

9. The method for preparing a solid oxide fuel cell electrolyte thin film according to claim 8, characterized in that, The solid-liquid phase molding process includes one or more combinations of casting, screen printing, spin coating, electrophoretic deposition, slurry 3D printing, dry molding, slip casting, centrifugal casting, sol-gel method, spraying, and spray pyrolysis; and / or, the electrolyte powder includes one of yttrium oxide-doped zirconium oxide, gadolinium oxide-doped cerium oxide, yttrium oxide-doped cerium oxide, and samarium oxide-doped cerium oxide; the binder includes one of ethyl cellulose, nitrocellulose, carboxymethyl cellulose, polyvinyl alcohol, and polyvinyl butyral; the solvent includes one of terpineol, 1,4-butyrolactone, glycerol, dibutyl phthalate, and tributyl citrate; and / or, the first sintering temperature is 800–1100°C; and / or, the thickness of the transition layer is 5–25 μm.

10. The method for preparing a solid oxide fuel cell electrolyte thin film according to claim 8, characterized in that, During the first vacuum sputtering coating process, the target sputtering power is 1–10 W / cm. 2 The process gas pressure is 0.3–2 Pa, the flow rate of the working gas Ar is 20–500 sccm, the flow rate of the working gas O2 is below 300 sccm, the O2 / Ar mixing ratio is 1 / 300–1 / 1, the sputtering rate is 20–300 nm / min, the target-substrate distance is 2–30 cm, the bias voltage is 0–-1200 V, the bias duty cycle is 1–100%, and the coating process is intermittent, achieved by intermittently switching on and off the working gases O2 and Ar. The ratio of process pause time to total process time is 1 / 50–1 / 3; the thickness of the self-healing layer is 100 nm–1 μm. During the second vacuum sputtering coating process, the target sputtering power is 0.01–3 W / cm². 2 The process gas pressure is 0.05–1 Pa, the flow rate of the working gas Ar is 20–500 sccm, the flow rate of the working gas O2 is below 300 sccm, the O2 / Ar mixing ratio is 1 / 300–1 / 1, the sputtering deposition rate is 0.5–50 nm / min, the target-substrate distance is 2–30 cm, the bias voltage is +200 V–-1200 V, and the bias duty cycle is 1–100%; the thickness of the dense layer is 50 nm–800 nm. The target material used in the first vacuum sputtering coating process or the second vacuum sputtering coating process includes one of the following: Y / Zr alloy, Gd / Ce alloy, Y / Ce alloy, Sm / Ce alloy, yttrium-doped zirconium oxide, gadolinium-doped cerium oxide, yttrium-doped cerium oxide, and samarium-doped cerium oxide. The vacuum sputtering coating type includes one or more combinations of DC sputtering, radio frequency sputtering, DC reactive sputtering, radio frequency reactive sputtering, and DC pulse sputtering.

11. The method for preparing a solid oxide fuel cell electrolyte thin film according to claim 8, characterized in that, Also includes: After the dense layer is formed, the resulting electrolyte film is subjected to a second sintering.

12. The method for preparing a solid oxide fuel cell electrolyte thin film according to claim 11, characterized in that, The second sintering temperature is 100-800℃ and the time is less than 10 hours.

13. The method for preparing a solid oxide fuel cell electrolyte thin film according to claim 8, characterized in that, Also includes: Before performing the first vacuum sputtering coating process, the substrate on which the transition layer is formed is subjected to ion cleaning.

14. The method for preparing a solid oxide fuel cell electrolyte thin film according to claim 13, characterized in that, Both the ion cleaning and the vacuum sputtering coating are performed at room temperature without heating.